(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Gestational age is age of unborn baby, defined in weeks as beginning from first day of last menstrual periodprior to conception. Estimation of gestational age and thereby forecasting Expected Date of Delivery is notonly concern of the Individual but it is invaluable in the diagnosis of intrauterine growth retardation of fetusand obstetric planning. Determination of age of a fetus by using various methods is required for medico legalpurposes in both civil and criminal matters. In present study we assesses Correlation between gestationalage and abdominal circumference in second trimester, The study of Correlation between gestational ageand abdominal circumference in second trimester by Ultrasonography was carried out and collected datawas tabulated according to weeks of menstrual cycle and were taken in centimeters. Standard deviationof abdominal circumference for each week was calculated. We found that Abdominal Circumference isstatistically highly significant and the regression equations derived for growth parameter for estimatinggestational age in a normally developing fetus, increase with gestational age, showed good correlation withgestational age.